1996
DOI: 10.1002/(sici)1097-0215(19960422)69:2<92::aid-ijc4>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 and prognosis in human breast cancer

Abstract: We have used immunohistochemical staining to assess the expression of cyclin D I in formalin-fixed sections of 345 breast carcinomas, dating back 20 years. Clinical follow-up data were available on all patients. Approximately 50% of the tumours showed excessive nuclear staining for cyclin DI as compared with normal epithelium. Some tumours showed strong cytoplas-mic staining in the absence of nuclear staining, and around 25% of the tumours were judged to be negative for nuclear cyclin D I. Contrary to expectat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
190
1
2

Year Published

1997
1997
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 297 publications
(222 citation statements)
references
References 13 publications
29
190
1
2
Order By: Relevance
“…Like two other studies (22,23), but unlike a third one (20), we found no association between cyclin D1 status and DNA ploidy. We were not able to study the association between positive estrogen receptor status and cyclin D1 overexpression, as has been documented by a number of other investigators (6,18,21,22).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Like two other studies (22,23), but unlike a third one (20), we found no association between cyclin D1 status and DNA ploidy. We were not able to study the association between positive estrogen receptor status and cyclin D1 overexpression, as has been documented by a number of other investigators (6,18,21,22).…”
Section: Discussionmentioning
confidence: 95%
“…Most previous reports also failed to demonstrate a correlation between cyclin D1 overexpression and size of the lesion, and no study has yet shown an association with axillary lymph node involvement (6, 18 -23). Likewise, the majority of published series failed to report a correlation with tumor grade (18 -22), although two groups reported a lower cyclin D1 positivity rate in high grade breast cancers (6,23). It is conceivable that the possible association with low grade may in part explain the favorable prognostic significance of cyclin D1 overexpression in breast cancer reported by some (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It contrasts with cyclin Dl, the other important G, cyclin, whose overexpression is known to correlate with the presence of oestrogen receptor (Gillet et al, 1996). A relationship was also found between p53 and cyclin E but this may be indirect as virtually all the carcinomas with p53 protein and cyclin E were poorly differentiated.…”
Section: Evaluation Carcinomasmentioning
confidence: 95%